Perencanaan Skenario Strategi Pemasaran di Konveksi The Xild Apparel - Aulawi, Hilmi; Rahmawati, Dewi; Misbah Syahbudin, Muhammad Khoirul (Jurnal Kalibrasi, 2024)
The problem currently occurring in the company is that currently the company only relies on acquaintances of the owners and workers there to carry out marketing, namely by marketing by word of mouth. This will of course lead to a narrow reach of consumers, unable to compete with similar companies and unable to adapt to external trends. Sales that occurred during the 12 months also experienced a fluctuating phase. Therefore, this company requires planning accompanied by the right strategy. The method used in this research is scenario planning. By using scenario planning, various scenarios can be prepared in the planning process, which allows them to be more flexible and remain focused on implementing an effective marketing plan. The research results showed that there were 4 scenario plans taken from two variables, namely clothing trends and competitors. The first quadrant of the scenario is responsive and adaptive, the second quadrant is operational efficiency, the third quadrant is innovative, and the last is differentiation. The scenario that should be used is the operational efficiency scenario because this will provide a wide consumer reach and also gain consumer trust directly through face-to-face meetings. Hybrid marketing conducted online and offline will provide flexibility to adapt strategies to changes in market trends or changes in consumer behavior. So the company can allocate resources according to needs.